2020
DOI: 10.1002/hep.31215
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Dynamics of Hepatic Sinusoid‐Associated Cells After Liver Injury

Abstract: Background & Aims: Hepatic sinusoidal cells are known actors in the fibrogenic response to injury. Activated hepatic stellate cells (HSCs), liver sinusoidal endothelial cells, and Kupffer cells are responsible for sinusoidal capillarization and perisinusoidal matrix deposition impairing vascular exchange and heightening the risk of advanced fibrosis. While the overall pathogenesis is well-understood, functional relations between cellular transitions during fibrogenesis are only beginning to be resolved. At sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 38 publications
3
62
0
Order By: Relevance
“… 29 In addition, 48 of these 300 genes were identified as top HSC state-defining genes during a CCl 4 treatment time course study in C57BL/6J mice. 30 …”
Section: Resultsmentioning
confidence: 99%
“… 29 In addition, 48 of these 300 genes were identified as top HSC state-defining genes during a CCl 4 treatment time course study in C57BL/6J mice. 30 …”
Section: Resultsmentioning
confidence: 99%
“…Generation of these data has been described before [32]. In short, female C57BL6/J mice were treated with vehicle or CCl 4 for 2 or 4 weeks (n = 3).…”
Section: Single-cell Rna Sequencing and Analysesmentioning
confidence: 99%
“… 15 , 16 A recent single-cell RNA-sequencing study showed that MFAP4 secreted by hepatic stellate cells was an integral part of the transcriptome in murine models of liver fibrosis and confirmed the MFAP4 gene as 1 of 4 hepatic expressed genes that are robust predictors of advanced fibrosis. 17 Observational follow-up studies of early-stage liver disease have shown that fibrosis is the most important prognostic factor in liver disease. 18 , 19 Biomarkers of liver fibrosis may therefore also provide prognostic information.…”
Section: Introductionmentioning
confidence: 99%